2012
DOI: 10.1161/circulationaha.112.097709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of QRS Duration and Morphology on Cardiac Resynchronization Therapy Outcomes in Mild Heart Failure

Abstract: Background-Cardiac resynchronization therapy (CRT) decreases mortality, improves functional status, and induces reverse left ventricular remodeling in selected populations with heart failure. We aimed to assess the impact of baseline QRS duration and morphology and the change in QRS duration with pacing on CRT outcomes in mild heart failure. Methods and Results-Resynchronization Reverses Remodeling in Systolic Left Ventricular Dysfunction (REVERSE)was a multicenter randomized trial of CRT among 610 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 282 publications
(104 citation statements)
references
References 33 publications
7
84
0
13
Order By: Relevance
“…24 LBBB is clearly more evident in early LVRR patients. 25,26 In our study, Groups B and C had a higher incidence of ischemic etiology. Several previous studies have shown less clinical and LV function improvement in ischemic patients, probably due to the presence of myocardial scar tissue in the vicinity of the pacing lead, limiting the extent of LVRR regardless of the extent of baseline dyssynchrony.…”
Section: Discussionsupporting
confidence: 45%
“…24 LBBB is clearly more evident in early LVRR patients. 25,26 In our study, Groups B and C had a higher incidence of ischemic etiology. Several previous studies have shown less clinical and LV function improvement in ischemic patients, probably due to the presence of myocardial scar tissue in the vicinity of the pacing lead, limiting the extent of LVRR regardless of the extent of baseline dyssynchrony.…”
Section: Discussionsupporting
confidence: 45%
“…7 The REVERSE study confirmed the importance of QRS duration and LBBB pattern in CRT outcomes. 26 With regard to our study, the sample size, the higher percentage of patients with nonischemic etiology and mean QRS >150 ms influenced our results.…”
Section: Discussionmentioning
confidence: 79%
“…Although the parameters based on the echo cardiography had been most anticipated, PROSPECT trial13 which was performed aiming to determine echo parameters to predict responders and nonresponders of CRT failed to find any parameters. On the other hand, subanalysis of major trials including COMPANION,4 MADIT‐CRT,14 or REVERSE15 revealed that the patients with QRS width ≥150 ms were likely to receive most benefit of CRT and LBBB pattern seemed to have better outcome than right bundle branch block or nonspecific block pattern. QRS width ≥150 ms was also an important predictor for responders in RAFT trial 12.…”
Section: Can We Predict the Effect Of Crt?mentioning
confidence: 99%